Comparison of fine needle aspiration cytology and core needle biopsy findings with excisional biopsy in breast malignancy (Journal of Pathology of Nepal, 2019)
Background: Fine needle aspiration cytology and core needle biopsy are reliable procedures for breast cancer detection. Core needle biopsy is an established alternative to surgical biopsy for diagnosis and prognostication. However, there may be a concern that core needle biopsy may be less reliable than excisional biopsy. The aim of this study was to compare the cytological/core needle biopsy finding with excisional histopathological diagnosis and determine their hormonal status.Materials and Methods: A prospective study of 65 patients was conducted after obtaining a detailed clinical data. The comparison of the fine needle aspiration cytology/core needle biopsy finding with excisional histopathological diagnosis of breast malignancy was carried out after data analysis. Their ER, PR and HER-2/neu status was also studied in available cases.Results: Out of the 65 cases of breast malignancy, 69.2% of cases had undergone fine needle aspiration, 60% cases core needle biopsy and 93.8% cases excisional biopsy. The most common carcinoma was invasive carcinoma of no special type. The diagnostic accuracy of fine needle aspiration and core needle biopsy was almost equal, however, core needle biopsy could assess the histological typing and biomarker status. The hormonal status was assessed in 69.23% cases, among them 35.6% cases were triple negative carcinomas.Conclusions: Core needle biopsy was superior to fine needle aspiration cytology in the diagnosis of breast lesions in terms of diagnostic accuracy. Thus, our result provides valuable prognostic information to guide the decision-making process for the treatment of a patient with invasive carcinoma.